Program Peningkatan Kesadaran Kesehatan Kulit pada Kelompok PKK di Kecamatan Way Tuba, Way Kanan, Lampung - Fahmi, Achmad Gus; Suryaneta; Handayani, Kiki Yuli; Putri, Tikarahayu; Sari, Indah Puspita; Auli, Winni Nur (Universitas Muhammadiyah Surakarta, 2023)
Way Tuba sub-district, Way Kanan is one of the areas where the majority of people work as farmers. This profession is very vulnerable to direct sunlight exposure which has a negative impact on human health, especially the skin and eyes. The worst danger due to UV exposure that most often occurs is Non-Melanoma Skin Cancer (NMSC). Awareness of these dangers is still not fully understood by the community, so a program is needed that can increase understanding of the risks of direct sun exposure and skin health. Lecturers of the Cosmetic engineering, ITERA organized a program to increase skin health awareness through several activities such as counseling for PKK groups, training in making simple skin care from natural ingredients around the house and initiating the planting of a family cosmetic garden in the yard. Utilization of natural ingredients around the house can overcome skin damage at a low cost. In addition, with the cultivation of plants that maintain skin health in the home yard, it can be used at any time as prevention not just as treatment. Therefore, it is necessary to understand the types and ways of using natural ingredients around the house for the community, especially the PKK Group as a driving cadre in each village. Based on the results of the questionnaire, this community service program can increase community understanding up to 90% of representatives from 13 PKK groups in each village in Way Tuba District. Some plants were also cultivated directly through the initiation of a family cosmetic garden in one of the residents' yards. This is expected to be a trigger for other PKK groups in utilizing yard land in caring for skin health.